Price setting and market structure: An empirical analysis of micro data - Fabrizio Coricelli; Roman Horváth (Charles University in Prague, Institute of Economic Studies (IES), 2008)
Most empirical studies on price setting that use micro data focus on advanced industrial countries. In this paper we analyze the experience of an emerging economy, Slovakia, using a large micro-level dataset that accounts for a substantial part of the consumer price index (about 5 million observations). We find that market structure is an important determinant of pricing behavior. The effect of market structure on persistence of inflation results from two conflicting forces. Increased competition may reduce persistence by increasing the frequency of price changes. In contrast, higher competition may increase persistence through inertial behaviour induced by the strategic complementarity among price setters. In our case study, we find that the latter effects dominate. Indeed, the dispersion of prices is higher while persistence is lower in the non-tradable sectors, suggesting that higher competition is not conducive to lower persistence. Furthermore, we find that the frequency of price changes depends negatively on the price dispersion and positively on the product-specific inflation. These results seem consistent with predictions of Calvo's staggered price model.
Keywords: D40; E31; 330; price setting; market structure; emerging markets; Inflation; Marktstruktur; Betriebliche Preispolitik; Preisrigidität; EU-Erweiterung; Schätzung; Slowakei